Pathogenic Role of Iron Deposition in Reticuloendothelial Cells during the Development of Chronic Hepatitis C. (4th April 2013) - Mitsuyoshi, Hironori; Yasui, Kohichiroh; Yamaguchi, Kanji; Minami, Masahito; Okanoue, Takeshi; Itoh, Yoshito
Abstract : Aim . Chronic hepatitis C (CHepC) is frequently associated with hepatic iron overload, yet mechanisms underlying iron-induced liver injury have not been elucidated. We examined the significance of iron deposition in hepatocytes (HC) and reticuloendothelial cells (REC) in CHepC. Methods . Stainable hepatic iron was scored according to the iron deposition pattern in 373 patients. The levels of serum soluble TNF- α receptor (sTNFR2) and hepatic hepcidin mRNA and the efficacy of phlebotomy were compared among patients with different iron deposition patterns. Results . Serum transaminase levels and hepatic scores of stage, grade, and steatosis were higher in patients with REC iron staining than in those without. REC iron scores were independently associated with advanced stage. Serum sTNFR2 levels were significantly higher in patients with REC iron than in those without. REC iron scores were independently correlated with sTNFR2 levels. Compared with patients without stainable iron, those with iron overload had decreased ratios of hepcidin mRNA to serum ferritin. The efficacy of phlebotomy was greater in patients with REC iron than in those without REC iron. Conclusions . The present results show the importance of REC iron for the development of CHepC and the therapeutic effect of phlebotomy in CHepC.